Life in Smokey's Smokehouse (Cimarron, New Mexico Cimarron Legend, 1992)
Article on Smokey's smokehouse Cafe in Ute Park, New Mexico.
Mater List Item # 8
File location is in the New Mexico File Cabinets
Keywords: McWilliams, Barry; Valentine, Teri; Pearson, David; Pearson, Lonnie; Pearson, Marcie; Pearson, Brian Thomas; Smokey's Cafe; Local History; Cafe; Barbeque; Cafe Owner; Ute Park, New Mexico; Eagle Nest, New Mexico; Logan, New Mexico